Application of Seed Mucilage Extracted from Lallemantia royleana as a Suspending Agent - A.Abdulrasool, Alaa; A.Naseer, Abdulmuttalib; A.Rahi, Firas (Iraqi Journal of Pharmaceutical Sciences, 2017)
The mucilage from the seeds of Lallemantia royleana family Labiatae was extracted and subjected to preformulation study for evaluation of its suitability for use as suspending agent. Furosemide suspensions were prepared using (1.5% w/v) of the extracted Lallemantia royleana mucilage, (1.5% w/v) chitosan and (0.35% w/v) xanthan gum. The mucilage was white in color and the average yield of dried mucilage obtained from L.royleana nutlets was 14 % w/w of the seeds used. It is sparingly soluble in water but swells in contact with it, giving a highly viscous solution. It is slightly acidic to neutral. It was found that the extracted natural mucilage of Lallemantia royleana exhibited a higher viscosity profile and it exhibited better mucoadhesive property in comparison to chitosan, Carbopol 934 and hydroxypropyl - methylcellulose. The result showed that the suspension of furosemide prepared with 1.5 % w/v of the extracted mucilage was found to be ideal and comparable with the other two preparations of xanthan gum 0.35% w/v and chitosan 1.5% w/v. The study revealed that the mucilage of Lallemantia royleana has good properties to be used as a suspending agent and the performance is comparable with that of chitosan and xanthan gum since it is of natural origin, non-toxic, and of good biocompatibility. Key words: mucilage; polymer; excipient; drug delivery; suspension; Lallemantia royleana.